Method of informative-analytical support of information security management based on the system approach - Домарєв, Дмитро Валерійович (Ukrainian Information Security Research Journal, 2014)
Informative-analytical support of information security management based on the system approach is used to unite the heterogeneous security means and the forces of different security specialists in order to fulfil the strategic tasks of Ukraine’s national information security. The model of logical and functional relations between the components of an information security management system (ISMS) is improved. The set of components named “Directions” is given a variable length. This provides the flexibility to the processes of analysis, prognostication and informative-analytical support for the decisions concerning information security. For the first time the information security management system data model is developed, that provides concerted processing and storage of operational tasks, knowledge and information security risks under the incompleteness of information. The data is structured according to the improved model of logical and functional relations between the components of an ISMS. For the first time the method of informative-analytical support for information security management is developed, which provides the system approach principles application in information security management. The method is based on the improved model of relations between the components of an ISMS, the developed information security management data model and the developed technique of current information security state estimation. An example of the developed method application in Ukraine’s banking system is presented. Recommendations for the scientific and practical use of the developed models and method are provided.